Uma abordagem, baseada na integração de arquétipos a mensagens HL7, para a comunicação de aplicações ubíquas no cuidado de saúde pervasivo - Menezes, Anderson Luiz (2011)
Due to the problems faced in Healthcare, this is heading towards a paradigm shift. This change suggests that the care is no longer focused exclusively on large hospitals and into the hands of specialized professionals. Thus, the goal is to distribute the Healthcare, making the patient play a key role in the process. Hence, the Pervasive Healthcare intends to provide the distribution of the model through the use of Information and Communication Technologies (ICT), enabling access to Healthcare anywhere and anytime. The creation of Pervasive Healthcare environments brings different challenges, which include the variety of devices to access information and the diversity of Hospital Information Systems (HIS) that may constitute such environment. In this context, the interoperability appears to be a fundamental requirement, since the information should be shared regardless of the existing heterogeneities. Aiming to provide this interoperability, different standards were set in order to facilitate the interaction between heterogeneous HISs. Some examples of these standards are the communication protocols developed by the Health Level Seven (HL7) committee, which are exclusive to the Healthcare domain. However, the standards set by the HL7 committee bring deficiencies to the clinical concepts representation and also has a relatively complex development process. An alternative to the knowledge representation in Healthcare is the use of archetypes, which are pieces of knowledge that show how to represent concepts or information of a given domain via computable expressions. Thus, this work presents an approach that integrates archetypes to HL7 v3 messages, for the communication of ubiquitous applications in Pervasive Healthcare. With the help of Model Driven Development, a process, which consists of activities designed to assist developers in adopting these standards, is defined. This approach makes use of modeling and partial code generation for simplifying and turning the development of the messages used in the environment more intuitive. The combination of these technologies enables an already established communication standard to improve its semantic quality, thus contributing to the achievement of the interoperability.